Hematological Analysis in Thai Samples with Deletional and Nondeletional HbH Diseases - Sakorn Pornprasert (2018)
© American Society for Clinical Pathology 2018. All rights reserved. Objectives To compare hematological parameters between deletional and nondeletional HbH diseases, and to investigate the correlation between HbH levels and hematological parameters within these 2 groups. Methods Samples of 43 deletional HbH diseases, which included 39 - SEA /-α 3.7, 4 - - SEA /-α 4.2, and 22 nondeletional HbH diseases (- - SEA /α cs α), were used in this study. Correlations between HbH levels and hematological parameters within these 2 groups were analyzed. Results The deletional HbH disease had higher levels of RBC counts, total Hb, pack cell volume (PCV), mean corpuscular Hb (MCH), mean corpuscular Hb concentration (MCHC), HbA, and HbA 2 than did the nondeletional HbH disease. A negative correlation between HbH and RBC counts was detected in the group of deletional HbH disease, while a positive correlation between HbH and RBC counts, total Hb, and PCV was found in the group of nondeletional HbH disease. Conclusions These results reflected that samples with nondeletional HbH showed more anemic features than those with the deletional HbH.